TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP IMPLEMENTASI AKAD WAKALAH BIL UJRAH PADA SISTEM PENJUALAN KONSINYASI (TITIP JUAL) UMKM AKSESORIS DI KECAMATAN MAKALE TANA TORAJA - Citra, Winny; Raehana, Syarifa; Zainal, Abdul Qahar; Lawang, Hasanna; Martini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the practice of the consignment sales system in Toraja accessories MSMEs in Makale District, Tana Toraja Regency and analyze the review of Sharia Economic Law on the implementation of the wakalah bil ujrah contract in this practice. This study uses a qualitative research type with a normative sociological approach. The research location is in Makale District, Tana Toraja Regency. The data sources used consist of primary data obtained through observation and interviews with MSMEs and shop owners, and secondary data obtained from books, journals, documents, and relevant literature. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used qualitative descriptive methods. The results of the study indicate that the practice of the consignment sales system in Toraja accessories MSMEs in Makale District is carried out through a mechanism of consignment of goods by MSMEs to shop owners to be marketed to consumers. This system provides benefits for both parties because MSMEs can expand their marketing reach without bearing shop operational costs, while shop owners receive commissions from product sales. Risk management is carried out based on mutual agreement, where damage that occurs within the limits of operational reasonableness is borne by the owner of the goods, while losses due to negligence of the store are the responsibility of the store. Based on the review of Sharia Economic Law, the practice of consignment sales is in accordance with the principles of the wakalah bil ujrah contract because there is an element of granting power of attorney from the MSME actor (muwakkil) to the store owner (wakil) to sell goods in return for a commission or commission that has been agreed upon.